Semiconductor nanowires self-assembled from colloidal CdTe nanocrystal building blocks: optical properties and application perspectives - DONEGAN, JOHN; RAKOVICH, YURY (My University, 2012)
Solution-based self-assembly of quasi-one-dimensional semiconductor nanostructures (nanowires) from quasi-zero-dimensional (quantum dots) colloidal nanocrystal building blocks has proven itself as a powerful and flexible preparation technique. Polycrystalline CdTe nanowires self-assembled from light-emitting thiol-capped CdTe nanocrystals are the focus of this Feature Article. These nanowires represent an interesting model system for quantum dot solids, where electronic coupling between the individual nanocrystals can be optically accessed and controlled. We provide a literature-based summary of the formation mechanism and the morphology-related aspects of self-assembled CdTe nanowires, and highlight several fundamental and application-related optical properties of these nanostructures. These include fundamental aspects of polarization anisotropies in photoluminescence excitation and emission, the electronic coupling between individual semiconductor nanocrystals constituting the nanowires, and more applied, waveguiding properties of CdTe nanowire bundles and anti-Stokes photoluminescence in a prototypical structure of co-axial nanowires. The optical properties of self-assembled CdTe nanowires considered here render them potential candidates for photonic nano-scale devices.
PUBLISHED
Keywords: colloidal nanocrystal; colloidal nanocrystal